Phytochemical and in silico studies for potential constituents from Centaurium spicatum as candidates against the SARS-CoV-2 main protease and RNA-dependent RNA polymerase. Issue 22 (17th November 2022) - Allam, Ahmed E.; Abouelela, Mohamed E.; Assaf, Hamdy K.; Sayed, Ahmed M.; Nafady, Alaa M.; El-Shanawany, Mohamed A.; Takano, Fumihide; Ohta, Tomihisa
Abstract: In the present study, a new secoiridoid glycoside lisianthoside II 1, along with seven known compounds 2–8, were isolated from Centaurium spicatum L. In-silico molecular docking and molecular dynamic simulation against SARS-CoV-2 Main protease (M pro ) and RNA-dependent RNA polymerase (RdRp) were conducted. The affinity docking scores revealed that 8 is the best bound ligand to M pro active site with binding energy of −14.9877 kcal/mol (RSMD = 1.16 Å), while 6 was the highest against RdRp (−16.9572 kcal/mol, RMSD = 1.01 Å). Moreover, the molecular dynamic simulation revealed that 8 with a (Δ G ) of −7.9 kcal/mol (RMSD value of 2.6 Å) and 6 (RMSD value of 1.6 Å) and binding free energy (Δ G ) of −7.1 kcal/mol achieved the highest stability over 50 ns of MDS inside the M pro and RdRp enzyme's active site, respectively. Hence, the isolated compounds could be a good lead for development of new leads targeting COVID-19. Graphical Abstract: UF0001